A Research Agenda for Helminth Diseases of Humans: Modelling for Control and Elimination - Basanez,M-G; McCarthy,JS; French,MD; Yang,G-J; Walker,M; Gambhir,M; Prichard,RK; Churcher,TS (PLOS Neglected Tropical Diseases, 2012)
Human helminthiases are of considerable publichealth importance in sub-Saharan Africa, Asia, and LatinAmerica. The acknowledgement of the disease burden dueto helminth infections, the availability of donated oraffordable drugs that are mostly safe and moderatelyefficacious, and the implementation of viable mass drugadministration (MDA) interventions have prompted theestablishment of various large-scale control and eliminationprogrammes. These programmes have benefited fromimproved epidemiological mapping of the infections, betterunderstanding of the scope and limitations of currentlyavailable diagnostics and of the relationship betweeninfection and morbidity, feasibility of community-directedor school-based interventions, and advances in the design ofmonitoring and evaluation (M&E) protocols. Considerablesuccess has been achieved in reducing morbidity orsuppressing transmission in a number of settings, whilstchallenges remain in many others. Some of the obstaclesinclude the lack of diagnostic tools appropriate to thechanging requirements of ongoing interventions andelimination settings; the reliance on a handful of drugsabout which not enough is known regarding modes ofaction, modes of resistance, and optimal dosage singly or incombination; the difficulties in sustaining adequate coverageand compliance in prolonged and/or integrated programmes;an incomplete understanding of the social,behavioural, and environmental determinants of infection;and last, but not least, very little investment in research anddevelopment (R&D). The Disease Reference Group onHelminth Infections (DRG4), established in 2009 by theSpecial Programme for Research and Training in TropicalDiseases (TDR), was given the mandate to undertake acomprehensive review of recent advances in helminthiasesresearch, identify research gaps, and rank priorities for anR&D agenda for the control and elimination of theseinfections. This review presents the processes undertakento identify and rank ten t